EPISTEMIC MODALITY MARKERS AT THE LEXEMIC LEVEL: THE ADVERB PROBABLY - Kosenko, Anna (University of Craiova, Faculty of Letters, 2025)
The article deals with epistemic modality markers at the lexemic level, namely the adverb probably. The research has clearly revealed that it has the highest frequency of use among epistemic modality markers at the lexemic level. This adverb is often used parenthetically, on the one hand revealing the phatic function of language and, on the other hand, bearing a definite semantic load. The combination between the epistemic adverb probably and non-assertive contexts is manifold.
Keywords: epistemic modality, marker, epistemic adverb